Quantification of diabetes consultations by the main primary health care nurse groups in Auckland, New Zealand. Issue 5 (8th January 2016) - Daly, Barbara; Arroll, Bruce; Sheridan, Nicolette; Kenealy, Timothy; Scragg, Robert
Abstract : Background: Diabetes prevalence continues to increase, with most diabetes patients managed in primary care.Aim: This report quantifies the number of diabetes consultations undertaken by primary healthcare nurses in Auckland, New Zealand.Methods: Of 335 primary healthcare nurses randomly selected, 287 (86%) completed a telephone interview in 2006–2008.Findings: On a randomly sampled day (from the past seven) for each nurse, 42% of the nurses surveyed ( n= 120) consulted 308 diabetes patients. From the proportion of nurses sampled in the study, it is calculated that the number of diabetes patients consulted by primary healthcare nurses per week in Auckland between September 2006 and February 2008 was 4210, with 61% consulted by practice, 23% by specialist and 16% by district nurses. These findings show that practice nurses carry out the largest number of community diabetes consultations by nurses. Their major contribution needs to be incorporated into future planning of the community management of diabetes.